2022
DOI: 10.3390/ijms23063189
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D May Protect against Breast Cancer through the Regulation of Long Noncoding RNAs by VDR Signaling

Abstract: Dietary vitamin D3 has attracted wide interest as a natural compound for breast cancer prevention and therapy, supported by in vitro and animal studies. The exact mechanism of such action of vitamin D3 is unknown and may include several independent or partly dependent pathways. The active metabolite of vitamin D3, 1α,25-dihydroxyvitamin D3 (1,25(OH)2D, calcitriol), binds to the vitamin D receptor (VDR) and induces its translocation to the nucleus, where it transactivates a myriad of genes. Vitamin D3 is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…A possible explanation of how vitamin D might affect breast cancer biology might be the tumor suppressive effects of vitamin D receptor catabolism, as a defect in the vitamin D receptor (e.g., CYP27B1 and CYP24A1 regulation) led to decreased signaling [ 33 ]. In addition, it could be shown that non-coding RNAs (lncRNAs) play an important role in the pathogenesis of breast cancer [ 34 ]. By modulating IncRNA, vitamin D could have a protective effect on the development of breast cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation of how vitamin D might affect breast cancer biology might be the tumor suppressive effects of vitamin D receptor catabolism, as a defect in the vitamin D receptor (e.g., CYP27B1 and CYP24A1 regulation) led to decreased signaling [ 33 ]. In addition, it could be shown that non-coding RNAs (lncRNAs) play an important role in the pathogenesis of breast cancer [ 34 ]. By modulating IncRNA, vitamin D could have a protective effect on the development of breast cancer [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could be shown that non-coding RNAs (lncRNAs) play an important role in the pathogenesis of breast cancer [ 34 ]. By modulating IncRNA, vitamin D could have a protective effect on the development of breast cancer [ 34 ]. However, by now these results could mostly be shown in vitro and in animal experiments, not in clinical trials [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of vitamin D supplementation has been investigated in different cancers [30][31][32][33] . However, its role in CRCLM is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous publications showed a positive correlation between cancer cell motility and the development of vessel co-option in CRCLM in vivo 12,27,28 , which is mediated by upregulation of runt related transcription factor-1 and actin-related protein 2/3 complex (RUNX1-ARP2/3) pathway 29 . Interestingly, vitamin D has been shown as a negative regulator of cancer cell motility in different types of cancers, such as thyroid 30 , breast 31 , ovarian 32 , and colorectal cancer 33 . The impact of vitamin D on cancer cell motility is yet to be investigated in CRCLM.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that calcitriol can modulate cell proliferation, induce apoptosis, and inhibit angiogenesis in various cancer types. [6][7][8] And some clinical trials have been conducted to evaluate its supplements for cancer treatment. [9][10][11] However, its precise effects on the gastric TME and the interplay between macrophages and gastric cancer cells within this context remain poorly understood.…”
mentioning
confidence: 99%